Tartariae sive magni chami regni tÿpus. - Ortelius, Abraham, 1527-1598 (Abraham Ortelius, 1584)
16th century Copper engraving handcolored with watercolor. Relief shown pictorially. Printed in cartouche in upper right corner: "Tartariae Sive Magni Chami Regni typus." Printed in North America: "L'Americle Vel Novi Orbis Pars." Printed in cartouche in lower left corner: "Continet hec tabula oem Tartariam, cum reliqua Asie, Orientalioris vsq, Oceanu Evum parte, Magno chamo obediente. Cuius imperium Obij fl: Kataia lacu; Volga fl; Mari Caspio, Chesel flu.; UBonte monte, Thebet regione, Caromoram fluuio, & Oceano terminator." Printed beneath cartouche in lower right corner: "Cum Privilegio." Printed next to cartouche in ocean: "Oceanus Scythicus dulcis est Plinio auctore, qui multas in eo insulas ese dicit, vt etiam M. Paul Venetus: sed neuter neg situm neg, numeru tradit." Printed beneath Japan or "Iapan": "Japan insula, "a M. Paulo Veneto Zipangri dicta, olim Chryse, a Magno Cham olim bello petita sed frustra." Printed in Tartaria beneath illustration of a man in a tent: "Magnus Cham (quod lingua Tartarorum Imperatorem Sonat) max imus Asie princeps." Latin description of Tartaria printed on verso with map number "92": "Qui Tartaros describere velit, multas riationes describat necesse est…" Written in pencil in upper right corner: "92." Depicts Russia, especially modern-day Siberia. Also illustrates the western part of North America, Japan, part of eastern Europe, part of northern China, northern India and part of modern-day Middle East. Shows the Bering Strait as the Anian Strait or "Stretto di Anian," Caspian Sea as "Mar de Bachu, olim Mare Caspium et Hyrcanum" and "Mar Maggoire." Descriptions of various regions and towns labeled in Tartaria included for Nepthalitaru, Tabor, Argon, Arsareth, Tangut and Turchestan. Of note, California is correctly shown as a peninsula and the "Mar Vermeio" is shown next to it on North America's west coast. Shows mountains, rivers and pictorial cities throughout. Includes illustrations of angels and birds surrounding cartouche in lower left, flowers and exotic birds around the title cartouche, ships in the sea and a large fish in the lower right as well as a warrior-leader in the upper left corner in front of a large tent. Scale c.a. 1:25,000,000. Abraham Ortelius (1527-1598) was a cartographer and publisher. He set up a business as a book dealer and map painter in Antwerp. He traveled a great deal, making his business successful by developing a large network of contacts around Europe. In 1564 he published a world map in eight sheets, marking the start of a long career in map publishing (Moreland and Bannister, 98). In 1570, Ortelius published the "first modern uniform atlas," the Theatrum Orbis Terrarum (1570) (Tooley, 476). Having combined a large collection of maps from various European cartographers, he had them engraved to a standard size (Moreland and Bannister, 98). He also commissioned Frans Hogenberg to create cartouches and illustrations for these maps, following the popular style of the Flemish Renaissance (Klemp, map 15). Multiple editions of this highly successful and influential atlas were published in many languages up to 1612. Of note, Ortelius credited other cartographers. Ortelius's other works include: "Egypt" (1565), "Asia" (1567), "Spain" (1570) and "Roman Empire" (1571) (Tooley, 476). This map was published as map 92 in the 1584 edition of Ortelius's "Theatrum Orbis Terrarum" (Koeman, 50). Source(s): Koeman, Cornelius, ed. "Alantes Neerlandici: Bibliography of Terrestrial, Maritime, and Celestial Books, Atlases and Pilot Books Published in the Netherlands up to 1880. Volume 3." Amsterdam: Theatrum Orbis Terrarum Ltd., 1970. Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.